Percentage of mesenchymal stem cells in high-grade glioma tumor samples correlates with patient survival - Shahar, Tal (Neuro Oncol, 2017)
BACKGROUND. Human mesenchymal stem cells (hMSCs) have been shown to reside as stromal cells in human gliomas as glioma-associated hMSCs (GA-hMSCs), but their biological role remains unclear. Because recent evidence indicates that GA-hMSCs drive tumor cell proliferation and stemness, we hypothesized that a higher percentage of GA-hMSCs in tumors predicts poor patient prognosis. METHOD. We determined the percentage of cells coexpressing GA-hMSC markers CD105+/CD73+/CD90+ from patients with newly diagnosed high-grade glioma and analyzed the association between this percentage and overall survival (OS) in 3 independent cohorts: fresh surgical glioblastoma specimens (cohort 1, N = 9), cultured tumor specimens at passage 3 (cohort 2, N = 28), and The Cancer Genome Atlas (TCGA) database. RESULTS. In all cohorts, patient OS correlated with the percentages of GA-hMSCs in tumors. For cohort 1, the median OS of patients with tumors with a low percentage of triple-positive cells was 46 months, and for tumors with a high percentage of triple-positive cells, it was 12 months (hazard ratio [HR] = 0.24; 95% CI: 0.02–0.5, P = .02). For cohort 2, the median OS of patients with tumors with a low percentage of GA-hMSCs was 66 months, and for tumors with a high percentage, it was 11 months (HR = 0.38; 95% CI: 0.13–0.9, P = .04). In the database of TCGA, the median OS times in patients with high and low coexpression levels of CD105/CD73/CD90 were 8.4 months and 13.1 months (HR = 0.4; 95% CI: 0.1–0.88; P = .04), respectively. CONCLUSIONS. The percentage of GA-MSCs inversely correlates with OS, suggesting a role for GA-MSCs in promoting aggressive behavior of gliomas.